Исследования поселения Грузское 8 в 2007 г. - Кравченко, Э.Е.; Петренко, А.Н.; Мирошниченко, В.В. (Археологічні дослідження в Україні, 2009)
Seasonal settlement Hruzke 8 is distinguished from the most of others in the Steppe Zone by its topography, being situated at the bottom of a deep gully. The research reveals that the site was a seasonal (spring—summer) point left by the nomads at the first half — the middle of the 9th c. The materials found at the settlement are represented by transport wares and handmade pottery, and several items made of metal and bone. The places of light surface structures have been discovered.